Sabry Musa's Lord of the Spinach Field (1987): A Critique of Post-Colonial Utopianism - Marwa Essam Eldin Fahmy Alkhayat (Arab Studies Quarterly, 2021)
The present study examines the aesthetic features of Sabry Musa's Lord of the Spinach Field (1987) through Karl-Heinz Bohrer's “Utopia of the Subject” to foreground Homo's quest for a wished-for yet unattainable reality. Post-Colonial Utopianism depicts man's inner turmoil to force an act of willful rethinking to enhance the “anticipatory consciousness” of a better life, a point interrogated within Ernst Bloch's Principle of Hope to propose the concept of the “Not-Yet-Become”: the not realized futuristic reality. Therefore, the interest is in utopia/dystopia historicities as analytical markers of historical inquiry to analyze specific space/time coordinates; post-colonial pitfalls of a technoscience dystopia. As such, the remarkable characteristic of Post-Colonial Utopianism is critique, and “Subjective Utopia” strives to achieve a breach in the teleological ideology of historical structures; thereby, transformation is the central aesthetic strategy of post-colonial critique.